The Garden and Beyond: the Dry Season, the Ok Tedi Shutdown, and the Footprint of the 2015 El Niño Drought. Issue 1 (7th March 2016) - Jorgensen, Dan
Abstract : This paper offers a snapshot of the 2015 El Niño drought among Min people in Papua New Guinea's West Sepik and Western Provinces. Local assessments of food, water, and health show variation between locations, but with an overall tendency for the drought's effects to spread from lower to higher elevations as the drought progresses. This zone is in the hinterland of the Ok Tedi Mine, and the drought's regional impact was intensified by Ok Tedi's abrupt closure when low water in the Fly River stopped shipments of concentrate and cut off fuel and food supplies. The decision to close the mine was accompanied by the mandatory 'repatriation' of workers and their families to 'home' communities in the drought‐stricken hinterland. This, combined with deteriorating regional links, has eroded the capacity of Min communities to weather the drought, suggesting that we must look beyond the garden when calculating El Niño's costs.